Nature's Classroom: Enhancing Student Literacy Skills through Immersive Learning Experiences - Abduh, Yunnisa Nabila Putri; Anwar, Rully Khairul; Lusiana, Elnovani (Socio Politica : Jurnal Ilmiah Jurusan Sosiologi, 2025)
Nature school is an educational institution that implements a learning model by nature. This learning model combines exploration and theory to provide balanced skills. This study aims to analyze the efforts to improve student literacy and identify the obstacles faced in its implementation at Nature School (Sekolah Alam) of Bandung. This research specifically discusses the effectiveness of literacy activities in the learning model with nature. The research approach used is a qualitative approach with a case study type. The results show that literacy activities in the nature learning model help improve students reading and writing skills. Each level has different achievements, but with the same process, including reading literature to gain initial knowledge, exploration of the surrounding environment to broaden horizons, and application of the results of reading and exploration into writing. The obstacles in this process include differences in student abilities, where there are students who read quickly and slowly, as well as difficulties in communicating what has been read and vice versa. Contribution: This study highlights the innovative integration of nature-based learning with literacy development, demonstrating that engaging students in their environment can significantly enhance their reading and writing skills.